Prevalence and biological impact of clinically relevant gene fusions in head and neck cancers - Emily L. Hoskins; Raven Vella; Julie W. Reeser; Michele R. Wing; Eric Samorodnitsky; Altan Turkoglu; Leah Stein; Elizabeth Breuning; Zachary A. Risch; Wilnelly M. Hernandez-Sanchez; Lianbo Yu; Michelle Churchman; et al. (npj Precision Oncology)
Abstract Head and neck cancer (HNC) is the seventh most common cancer worldwide. Currently-approved systemic therapies include chemotherapy, anti-EGFR antibodies, and PD-1 immunotherapy, with few genomic-based targeted therapies. Gene fusions involving cancer-driving kinase genes such as FGFR, NTRK, and ALK are clinically targetable in other solid tumors; however, there is limited knowledge about their prevalence in HNC. Here, we describe the genomic landscape and the biological impact of oncogenic fusions in a combined dataset of over 13,000 HNC tumors (excluding salivary gland tumors). We identified 66 cases (2.8%) harboring oncogenic fusions, including previously-reported FGFR3 fusions (n = 19) and gain-of-function EGFR fusions (n = 6). Fusion-positive HNC had significantly higher gene expression and higher prevalence of human papillomavirus than fusion-negative HNC (p < 0.001). Tumors with FGFR alterations were associated with enriched cell proliferation and higher abundance of NK cells and CD8+ T cells compared to wildtype. Our results provide expanded therapeutic opportunities for patients with HNCs.